2004
DOI: 10.1038/nature02784
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of power-law flow in the Mojave desert mantle

Abstract: Studies of the Earth's response to large earthquakes can be viewed as large rock deformation experiments in which sudden stress changes induce viscous flow in the lower crust and upper mantle that lead to observable postseismic surface deformation. Laboratory experiments suggest that viscous flow of deforming hot lithospheric rocks is characterized by a power law in which strain rate is proportional to stress raised to a power, n (refs 2, 3). Most geodynamic models of flow in the lower crust and upper mantle, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
280
3
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 299 publications
(303 citation statements)
references
References 25 publications
19
280
3
1
Order By: Relevance
“…However, steady-state CEH models are inconsistent with observations of spatially broad (> 100 km), time-variable, postseismic deformation following large earthquakes (e.g., Nur and Mavko, 1974;Hetland and Hager, 2003;Pollitz, 2003;Freed and Bürgmann, 2004;Freed et al, 2006;Ryder et al, 2007). Models for time-dependent earthquake-cycle deformation have generally focused on either the diffuse deformation of a linear viscoelastic subseismogenic layer (e.g., Thatcher, 1983;Savage, 1990;Dixon et al, 2002Dixon et al, , 2003Ergintav et al, 2002;Segall, 2002;Hilley et al, 2005, Motagh et al, 2007 or localized shear on a down-dip extension of the coseismic fault zone (e.g., Marone et al, 1991;Bürgmann et al, 2002), whereas recently more postseismic models have incorporated both (e.g., Freed et al, 2006;Johnson et al, 2009).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, steady-state CEH models are inconsistent with observations of spatially broad (> 100 km), time-variable, postseismic deformation following large earthquakes (e.g., Nur and Mavko, 1974;Hetland and Hager, 2003;Pollitz, 2003;Freed and Bürgmann, 2004;Freed et al, 2006;Ryder et al, 2007). Models for time-dependent earthquake-cycle deformation have generally focused on either the diffuse deformation of a linear viscoelastic subseismogenic layer (e.g., Thatcher, 1983;Savage, 1990;Dixon et al, 2002Dixon et al, , 2003Ergintav et al, 2002;Segall, 2002;Hilley et al, 2005, Motagh et al, 2007 or localized shear on a down-dip extension of the coseismic fault zone (e.g., Marone et al, 1991;Bürgmann et al, 2002), whereas recently more postseismic models have incorporated both (e.g., Freed et al, 2006;Johnson et al, 2009).…”
Section: Introductionmentioning
confidence: 91%
“…For example, in the context of earthquake-cycle models assuming a single relaxation timescale, analysis of postseismic deformation suggested upper mantle effective viscosities of, or less than, 10 18 Pa s (e.g., Pollitz et al, 2001) whereas late in the earthquake-cycle deformation has been interpreted as consistent with viscosities of a subseismogenic layer exceeding 10 19 Pa s (e.g., Hilley et al, 2005;Meade and Hager, 2005). More recently, the analysis of postseismic deformation signals has led to the suggestion that single relaxation timescale models may not be sufficient to describe behavior within the postseismic regime alone (e.g., Pollitz et al, 2001;Pollitz, 2003Pollitz, , 2005Freed and Bürgmann, 2004;Ryder et al, 2007;Hearn et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…flow may sufficiently describe both processes due to the similarity of the timescales over which they take place (James et al, 2009). There is the additional complication that afterslip must be accounted for in post-seismic studies (Ingleby and Wright, 2017), but in general, the changing deformation rates observed during an earthquake cycle suggest that the Earth either follows a power-law rheology (Freed and Burgmann, 2004;Freed et al, 2006), or a rheology comprising several different 820 relaxation times (Pollitz, 2005;Hetland and Hager, 2006). Is there a single rheological law that can explain GIA, post-seismic deformation, intra-plate deformation, and deformation in response to sediment or lake loading (Gilbert, 1890;Dickinson et al, 2016)?…”
Section: Low Viscosity Regionsmentioning
confidence: 99%
“…Experimentally derived flow laws suggest relatively low long-term strength for the lower crust, particularly with respect to the middle crust and uppermost mantle, when the latter is dry (e.g., Brace and Kohlstedt, 1980;Kohlstedt et al, 1995). In contrast, a relatively strong lower crust is suggested by post-seismic relaxation studies (e.g., Pollitz et al, 2001;Freed and Bürgmann, 2004;Thatcher and Pollitz, 2008) and the presence of earthquakes in the lower crust (e.g., Jackson, 2002;Reyners et al, 2007). Generalization of lower-crustal rheology is difficult to assess because of its compositional heterogeneity.…”
Section: Introductionmentioning
confidence: 99%